National Partnership for Maternal Safety: Consensus Bundle on Venous Thromboembolism. Issue 1 (February 2017) - D'Alton, M. E.; Friedman, A. M.; Smiley, R. M.; Montgomery, D. M.; Paidas, M. J.; D'Oria, R.; Frost, J. L.; Hameed, A. B.; Karsnitz, D.; Levy, B.S.; Clark, S. L.
Abstract : (Abstracted from Anesth Analg, 123(4):942–949, 2016) According to the World Health Organization, 14.9% of maternal deaths in developed nations such as those of Europe and North America, Australia, New Zealand, and Japan are thought to involve embolism. In the United States alone, per the Centers for Disease Control and Prevention (2006–2010), approximately 9.3% of pregnancy-related deaths are a result of thrombotic pulmonary embolism.